Epiphany. - Cheng, Wan Yan. (2010)
Epiphany is a short film produced by a student group, Raison d'être Productions, as their Final Year Project. Raison d'être Productions is made up of 4 final year students from the Wee Kim Wee School of Communication and Information. The duration of the entire project took approximately nine months, under the supervision of Ms. Nikki Draper.